2000
DOI: 10.4049/jimmunol.165.9.5211
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 Mitogen-Activated Protein Kinase in Rhinovirus-Induced Cytokine Production by Bronchial Epithelial Cells

Abstract: The stress-activated protein kinase p38 plays a central role in the regulation of cytokine biosynthesis by various cell types in response to a wide range of stimuli. Because the local inflammatory response and the infiltration of neutrophils is thought to contribute to the symptoms and sequelae of rhinovirus infection, we investigated the role of p38 kinase in cytokine and chemokine elaboration in airway epithelial cells infected with human rhinovirus. Rhinovirus-39 infection of BEAS-2B cells resulted in synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 41 publications
9
119
0
1
Order By: Relevance
“…To confirm these observations and to elucidate the impact of cell signaling on cytokine synthesis in our model, cell signaling inhibition experiments have been performed using MAPK inhibitors PD98059, wortmannin, and SB-239063 (15). From these experiments, we learned that particularly PI3K plays a role in the transduction pathway triggered by S. aureus hemB mutants and trypsin for gene transcription of IL-8.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…To confirm these observations and to elucidate the impact of cell signaling on cytokine synthesis in our model, cell signaling inhibition experiments have been performed using MAPK inhibitors PD98059, wortmannin, and SB-239063 (15). From these experiments, we learned that particularly PI3K plays a role in the transduction pathway triggered by S. aureus hemB mutants and trypsin for gene transcription of IL-8.…”
Section: Discussionmentioning
confidence: 81%
“…MAPKs were inhibited by pretreatment with either PD98059 (Calbiochem) at a concentration of 50 M and wortmannin (Calbiochem) at a concentration of 100 nM or the selective p38 inhibitor SB-239063 (trans-1-(4 hydroxycyclohexyl)-4-(fluorophenyl)-5-(2-methoxy-pyrimidin-4-yl) imidazole) at a concentration of 30 M, 30 min before challenge with bacterial supernatants (BioSource International) (15).…”
Section: Stimulation Experimentsmentioning
confidence: 99%
“…Treatment with p38 kinase inhibitor (SB203580) shows a suppressed production of inflammatory mediators such as TNF, IL-1, IL-6, CXCL8/IL-8, and GM-CSF (14). p38 kinase is essential for virus-induced cytokine production by bronchial epithelial cells including IL-6, IL-8, and GM-CSF (15)(16)(17). We have shown that p38 kinase is involved in the hyperinduction of TNF-␣ expression in H5N1-infected macrophages (18), although the mechanisms underlying this hyperinduction of cytokine by H5N1 influenza virus have not been elucidated.…”
Section: Induction Of Proinflammatory Cytokines In Primary Humanmentioning
confidence: 99%
“…Rhinovirus infection of the bronchial epithelium induces expression of numerous proinflammatory genes (55)(56)(57)(58). Induction of nuclear factor (NF)-kB and other transcription factors has been clearly demonstrated with several viruses including HRV, RSV, and influenza (59)(60)(61)(62)(63)(64).…”
Section: Virusesmentioning
confidence: 99%